Analysis of Spatial Concentration of Accommodation Establishments Using Machine Learning Techniques and Spatial Analysis Tools - PARRA, Helien; VALDERRAMA, Diana M. Ayala; MORENO, Sebastián (Journal of Environmental Management and Tourism, 2022)
Tourism as an economic activity is influenced by social dynamics that can be measured by spatial analysis processes where phenomena such as concentration, trajectory and extension are evidenced, which can guide policy makers effectively for decision-making. In this document, the results of a study of spatial analysis of the concentration of accommodation establishments in the department of Boyacá, Colombia are presented in order to identify the correlation that exists between the territorial concentration, the natural attractions of the department and the type of establishment. It was found that there is evidence of a strong concentration in five clusters associated with three municipalities of the department's offer, however it is observed that statistically there is a high level of dispersion of the establishments explained by the road corridors and a growing development towards the natural attractions which are not fully covered by the current offer.